Evaluation of the Protoscolicidal Activity of Humulus lupulus Methanolic Extracts on Echinococcus granulosus Sensu Stricto - Albani, Clara Maria (2024)
Te larval stage of the parasite Echinococcus granulosus sensu lato (s.l) is responsible for cystic echinococcosis (CE), a long-term infection afecting humans and animals worldwide, and constitutes a serious public health concern. If left untreated, CE can cause serious damage to multiple organs, especially the liver and lungs. Regarding the treatment, in the last few years, the use of pharmacological treatment has increased, suggesting that in the future, drug therapy may replace surgery for uncomplicated cysts.However, the only available anthelmintic drug to treat this infection is the albendazole, which has an efcacy that does not exceed 50%. On the basis of the above-mentioned evidence, new and improved alternative treatments are urgently needed. Te use of natural products and their active fractions and components holds great promise as a valuable resource for the development of novel and efective therapies. Hop (Humulus lupulus L.) is a bittering agent in the brewing industry for which the sedative, digestive, anti-infammatory, and antimicrobial efects have been reported. Te purpose of this study was to assess the in vitro efcacy of methanolic extracts from the leaves of hop varieties against E. granulosus sensu stricto (s.s) protoscoleces. Varieties Mapuche and Victoria caused a stronger protoscolicidal efect compared to the Bullion, Cascade, and Traful varieties (P < 0.01),coinciding with their highest content of favonoids, total polyphenols, and saponins. Te viability of protoscoleces treated with the varieties Mapuche and Victoria decreased to approximately 50% at days 5 y 8, respectively, showing alterations such as soma contraction and impaired microtriches. After 18 days of treatment with both varieties, protoscoleces were completely altered bothstructurally and ultrastructurally. In conclusion, the methanolic extracts of the H. lupulus varieties Mapuche and Victoria demonstrated a marked in vitro efect against E. granulosus s.s. protoscoleces. Te beer-making industry exclusively uses hop cones, leaving behind large amounts of hop leaves as an agricultural by-product that is not being utilized. On the basis of our study,we propose that hop leaves could also be used as a source of secondary metabolites with anthelmintic activity